Using Qualitative Methods as a Needs Analysis for Developing a Creative Writing Course: A Thematic Analysis - Hewa Ali Faqe Rasool; Fatimah Rasheed Hasan Al Bajalani (Zanco Journal of Humanity Sciences)
Designing a creative writing (CW) course involves a lengthy, non-linear and multifaceted process. Needs analysis can be used as a starting point for data collection to explore the needs of the course from the perspective of the involved key players and the related areas. This present study is the first round of needs analysis which is part of a larger PhD project. It uses qualitative methods of data collection, namely, non-participant unstructured observations and semi-structured interviews as the first round of data collection at the University of Birmingham (UoB). Thematic analysis has been used to interpret the data and categorise the recurring themes inductively, which will later be compared to the Subject Benchmark of Creative Writing in the UK. The results of this study will be used in the second round of data collection for needs analysis at Salahaddin University-Erbil (SUE) in the larger project that aims to design a CW course at English departments at SUE in the Kurdistan of Iraq (KRI).